2018
DOI: 10.1007/s10863-018-9769-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of odor-induced c-Fos expression of juxtaglomerular activity following maintenance of mice on fatty diets

Abstract: Diet-induced obesity (DIO) decreases the number of OMP+ olfactory sensory neurons (OSN) in the olfactory epithelium by 25% and reduces correlate axonal projections to the olfactory bulb (OB). Whether surviving OSNs have equivalent odor responsivity is largely unknown. Herein, we utilized c-fos immediate-early gene expression to map neuronal activity and determine whether mice weaned to control (CF), moderately-high fat (MHF), or high-fat (HF) diet for a period of 6 months had changes in odor activation. Diet-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“… 24 Moreover, HFD can induce the functional impairment of mitral cells 56 and also reduce the activation of specific populations of neurons (juxtaglomerular/cFos+ cells) in the MOB. 57 …”
Section: Discussionmentioning
confidence: 99%
“… 24 Moreover, HFD can induce the functional impairment of mitral cells 56 and also reduce the activation of specific populations of neurons (juxtaglomerular/cFos+ cells) in the MOB. 57 …”
Section: Discussionmentioning
confidence: 99%
“…The excitability of those cells is also impaired. Under olfactory activation, juxta-glomerular cells surrounding the lateral glomerulus exhibited a loss of activity that was stronger for HFD than for mild FD, whereas juxta-glomerular cells surrounding the medial glomerulus were equally impaired for both diets (Fardone et al, 2019). No effect in MOB neurogenesis was reported after 8 months of HFD (Lietzau et al, 2020), on the other hand, a reduction of neurogenesis was reported in the T2D model of Goto-Kakizaki rats (Lietzau et al, 2018).…”
Section: The Main Olfactory Bulbmentioning
confidence: 91%
“…Similar effects on the mucosa are obtained using a high-fat diet (HF; 60%) or moderately high-fat diet (MHF;32%). Both conditions show an increase of microglial marker Iba-1 and a decrease in the number of ORNs in the OM due to apoptosis (Thiebaud et al, 2014;Fardone et al, 2019). The consequence of the reduced number of ORN is a decreased number of axonal projections to the glomerulus.…”
Section: The Olfactory Mucosamentioning
confidence: 99%
See 2 more Smart Citations